INVENTORY OF ARECACEAE FAMILY SPECIES IN THE LEMBAH BUKIT MANJAI TROPICAL RAINFOREST BIODIVERSITY PARK - Ramadhan, Muhammad Nazhief; Nurtamara, Luthfiana; Rezeki, Amalia (Biospecies, 2026)
The Arecaceae family holds significant ecological and economic value and is widely distributed in tropical regions, including Indonesia. This study aimed to inventory the Arecaceae species found in the Lembah Bukit Manjai Tropical Rainforest Biodiversity Park. A descriptive exploratory method was employed using field research and purposive sampling techniques. Data collection involved direct observation, morphological documentation, and species identification based on taxonomic references. The results identified five Arecaceae species: Arenga pinnata, Calamus manan, Caryota mitis, Calamus zollingeri, and Licuala spinosa. Species distribution was influenced by abiotic environmental factors such as light intensity, temperature, humidity, and soil pH. Calamus manan was the most dominant species, while Caryota mitis was the least encountered due to its low ecological tolerance. This study underscores the importance of biodiversity conservation and the use of inventory data as a foundation for sustainable tropical ecosystem management. Furthermore,  it contributes to the development of local taxonomic databases and documentation of potentially endemic species in South Kalimantan.